Understanding the interplay between COVID-19 and diabetes: insights for the post-pandemic era - Xuefei Zhao; Linlin Jiang; Linlin Jiang; Wenjie Sun; Shanshan Tang; Xiaomin Kang; Qing Gao; Qing Gao; Zehua Li; Zehua Li; Xuedong An; Fengmei Lian (Frontiers in Endocrinology)
The global pandemic caused by the SARS-CoV-2 virus has had a profound impact on the onset, progression, and management of diabetes, posing significant challenges to healthcare systems worldwide. This review elucidates the multifaceted impact of SARS-CoV-2 on diabetes mellitus, emphasizing the increased complexity of glycemic management in patients with SARS-CoV-2 infection following viral infection in the postpandemic era. In this study, we examined the diverse effects of the SARS-CoV-2 virus on individuals with diabetes. These effects included an elevated risk of morbidity, erratic fluctuations in blood glucose levels, the emergence of complications associated with diabetes, and the emergence of challenges related to self-management of the disease. From a mechanistic perspective, we investigated the following factors: SARS-CoV-2-mediated direct damage to islet beta cells, dysregulation of the RAAS system, impairment of islet function by oxidative stress, and the effects of the integrated stress response, stress response, and reduced adiponectin levels on insulin utilization efficiency and glucose metabolism. Furthermore, viral effects extend to diabetic complications and cardiovascular risk factors, such as coagulation abnormalities, hypertension, and lipid metabolism. This results in an exacerbation of the development of diabetic complications. This review highlights the urgent need for refined management strategies for patients with diabetes during the pandemic and in the later stages of COVID-19. Additionally, there is a need for integrated management strategies to mitigate the impact of COVID-19 on the long-term outcomes of patients with diabetes.